A DESCRIPTIVE STUDY ON TEACHING LEARNING PROCESS OF ENGLISH AT SDN 2 SINDON NGEMPLAK BOYOLALI: AN EDUCATIONAL ETHNOGRAPHY - WULANDARI, DWI ASTUTI (2011)
This research aims at describing the teaching learning process of English at the fifth year of SDN 2 Sindon Ngemplak Boyolali. It is conducted to describe the process of teaching learning process reflecting and the strenghts and weaknesses at SDN 2 Sindon. In this research the data are derived from event, information and document. There are three techniques in collecting the data namely: interview, observation, and document. The data achieved from information related to the teaching learning process of English, in form of the field note, interview scripts and document. The results of the research show that are: 1.Process of teaching learning English reflecting at SDN 2 Sindon Ngemplak Boyolali especially at the fifth year, includes: a. Description of research location b. The objective of teaching learning c. The material d. Method of teaching English e. Evaluation. 2. The strength and the weaknesses of English teaching learning process, includes: a. Strengths in English teaching learning process good relationship between the teacher and the students, the teacher's role, are students have high interest in English, students are more communicative in the class and the students are more motivated in learning. b. The weaknesses in English teaching learning process are the teacher uses Indonesian language, the teacher does not teach based on syllabus and lesson plan, the students are limited vocabulary, the students not dicipline in the classroom, the students were still nerveous, less English touch in the classroom.